Bidirectional CPW Fed Quad-Band DRA for WLAN/WiMAX Applications. (3rd June 2022) - Iqbal, Assad; Owais, Owais; Kaabar, Mohammed K. A.; Shakir, Mustafa; Ullah, Inam; Khan, Aftab Ahmad; Khan, Abd Ullah; Rehman, Ateeq Ur
Abstract : Due to the size constraint, antennas with compact size are required that can support multibands with single radiating element. Dielectric resonator antenna (DRA) can support multiple modes with good efficiency and gain using single radiating element. In this paper, a quad-band DRA is proposed for WLAN/WiMAX bands using a single CPW feed. Out of four bands, WLAN (2.37-2.55) GHz, (5.15-5.35) GHz, and (5.6-5.83) GHz are achieved by the excitation of fundamental and higher-order modes whereas WiMAX (3.58-3.72) GHz band is achieved by dielectric loading of the DR. Dielectric loading makes it possible to operate the antenna at desired frequency band. Due to the partial ground plane and single coplanar waveguide (CPW) feed radiation pattern of the proposed antenna is bidirectional. The design is efficient in terms of radiation efficiency. Simulated and measured results show that it can be a suitable candidate for WLAN and WiMAX applications.